The Influence of SaLDI Learning Model (Stimulation, Learning Community, Discovery, Inferring) on Activity, Motivation, and Learning Outcomes of Biology of High School Students - Suhardi Aldi; Adnan; Andi Asmawati Azis (Jurnal Penelitian Pendidikan IPA, 2024)
The study aimed was to determine the effect of the SaLDI learning model integrated with TPACK on student activity, motivation and learning outcomes. This type of research is an experiment with a posttest-only control group design. The sampling technique is using random sampling. The sample in this study was XI 5 class as the control class and XI 6 as the experimental class, each class totalling 32 students at SMAN 14 Makassar. The instruments used were observation sheet of learning activity, questionnaire of learning motivation, learning outcome test with multiple choice type. Research data analysis includes descriptive and inferential analysis and uses non-parametric testing with mann whithney test using SPSS type 25.0. The results of descriptive analysis showed that implementing of the TPACK-integrated SaLDI learning model in the experimental class had the ability of active learning activities, very high learning motivation and good learning outcomes. The results of the infrential analysis show that the alpha significance is smaller than 0.05. So, there is a positive influence of SaLDI learning model integrated with TPACK on the activity, motivation and learning outcomes of Biology students at SMAN 14 Makassar.